ICD indication in hypertrophic cardiomyopathy: which algorithm to use? - Santos-Veloso,Marcelo Antônio Oliveira (2022)
SUMMARY OBJECTIVE: This study aimed to evaluate the agreement in the indication of implantable cardioverter-defibrillators in patients with Hypertrophic cardiomyopathy, as per the 2014 European Society of Cardiology and 2020 American Heart Association recommendations, and evaluate fragmented QRS as a predictor of cardiovascular outcome. METHODS: Retrospective cohort with 81 patients was evaluated between 2019 and 2021. Patients with hypertrophic cardiomyopathy ≥16 years old were included. Exclusion criteria include secondary myocardiopathy and follow-up <1 year. Kappa coefficient was used to determine the agreement. Survival and incidence curves were determined by Kaplan-Meier method. A p<0.05 was considered significant. RESULTS: The fragmented QRS was identified in 44.4% of patients. There were no differences between patients with and without fragmented QRS regarding clinical parameters, echocardiography, fibrosis, and sudden cardiac death risk. During follow-up of 4.8±3.4 years, there was no sudden cardiac death, but 20.6% patients with implantable cardioverter-defibrillator had at least one appropriate shock. Three of the seven appropriate shocks occurred in European Society of Cardiology low- to moderate-risk patients. Three shocks occurred in moderate-risk patients and four in American Heart Association high-risk patients. Overall recommendations agreement was 64% with a kappa of 0.270 (p=0.007). C-statistic showed no differences regarding the incidence of appropriate shock (p=0.644). CONCLUSION: sudden cardiac death risk stratification algorithms present discrepancies in implantable cardioverter-defibrillator indication, both with low accuracy.